Assessment of the central hearing system of sport divers - Hausmann, Daniel; Laabling, Renée-Sybille; Hoth, Sebastian; Plinkert, Peter K.; Klingmann, Christoph (Undersea and hyperbaric medicine, 2011)
OBJECTIVE: To investigate the effect of regular scuba diving on central processing sequences of sport divers who have no history of noise exposure or ear-related accidents using a comprehensive topographic examination of the central hearing system. - DESIGN: Cross-sectional controlled comparison study. - SETTINGS: General sports diving community. - PARTICIPANTS: 81 sport divers with a mean of 300 dives each were compared with a control group of 81 non-divers. - MAIN OUTCOME MEASURE: The participants were classified into three age groups. Hearing test results were combined for both ears. Examination included brainstem evoked response audiometry (BERA), cortical evoked response audiometry (CERA) and dichotic listening tests to screen for retrocochlear and central hearing disorders. Testing of brainstem latencies was performed in a gender-dependent manner. - RESULTS: BERA showed a pathological extension of the I-V-latency in one diver. Magnetic tomographic imaging ruled out brainstem lesions. No reason for the measured latency could be detected. All other latencies (I-III, III-V and I-V) in both gender groups were within normal limits. No statistically significant differences between divers and non-divers could be detected. Dichotic listening showed no clinical abnormalities in any of the participants, but in the age group 18-29 years divers performed significantly better than non-divers (p = 0.01). CERA revealed no significant differences between divers and non-divers in the age group 18-29 years and 30-39 years, whereas divers in the age group 41-50 demonstrated significantly better test results (p = 0.045) (difference of the means: 4.18 dB). - CONCLUSION: Dichotic listening and CERA did not reveal a significant reduction of central hearing performance in divers. Persistent on-shore BERA wave latency prolongations that were present in one study could not be confirmed in our study group. This first comprehensive topographic examination of the central hearing system of divers showed no abnormalities.
Gesehen am 23.09.2022 (nur PubMed-Eintrag)